The location advantages and persistence of the performance for the Taiwan logistic company: A case study - Chiu-Ming Hsiao; Lai Pin-Reuy; Sun Li-Yun; Tsai Yun-Jean (Cogent Business & Management, 2018)
This study empirically analyzes the persistence of the performance for the Taiwanese logistic company. It is the first study to address the hot hand effect on the performance of logistic stations. Generally, the well-performed stations (Winner) will still have a better performance in the following period; the poor-performed stations (Loser) will stay in the worst group. Moreover, we find there is a strong evidence of location advantage for the business stations which supports the discussion of Hernández and Pedersen. It reveals that a non-metropolitan station is well performed rather than the metropolitan station. Either to increase the number of cargo or to decrease the number of workers will promote the performance of the company. Our empirical results can also be extended to the logistic companies in the emerging markets and transition economies. Policy-makers can provide some incentives to make the logistics industry more vigorous development and create economic prosperity.
Keywords: 650